Upaya Peningkatan Kebersihan Jalan Nafas Pada Pasien Dengan Post Op Anterior Stabilisasi Spondilitis Tuberkulosis - LESTYA NALA PRAYA, EDGAR; , Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB (2017)
Introduction: spondylitis tuberculosis is an infectious disease caused by mikrobakterium tuberculosis that attacks the spine. The disease is spread through hematogenous discus and including skeletal manifestations of tuberculosis are common in spinal disorders. if the client affected by this disease will experience symptoms of pain and respiratory disorders. One experienced respiratory disorders are ineffective clearance of airway obstruction of respiratory tract infections that arise because tubeculosis microbakterium. Methods: The case study approach is descriptive method to collect data, analyze the data and draw conclusions. How to use such interviews, observation, and physical examination and medical progress notes Rakam. Results: During the study on the client, observing the development of health and physical examination data obtained 2 during the 3 days of the subjective and objective, subjective and objective data from nursing diagnoses appear. Priority nursing diagnosis is not effective airway clearance related to or obtruksi accumulation of secretions in the respiratory tract. This diagnosis if not promptly treated will cause complications. Nursing plans to handle the clearance of airway during 3x24 hours aimed at making the airway clear of sputum and breath patents. Chest physiotherapy nursing actions to achieve the goals of the care plan and evaluation showed clean and patent airway. Discussion: 3x24 hours after the act is expected to be effective airway criteria specified results. Chest physiotherapy is a technique of postural drainage, vibration and percussion, nebulizer and effective cough is very useful combination of actions to overcome airway clearance. Conclusion: actions taken to overcome cleanliness proven airway in patients with tuberculosis spondylitis. Keywords: tuberculosis spondylitis, chest physiotherapy, nursing actions.